By any other name: early modern expertise and the problem of anachronism. (2nd January 2019) - Ash, Eric H.
ABSTRACT: The idea of expertise in early modern Europe has attracted significant attention from historians of science and technology in recent years. Some find the term useful in describing the rise of a productive and flexible combination of practical and theoretical knowledge, for which a contemporary word did not yet exist. Others criticize the term as a pernicious anachronism that not only distorts our understanding of the pre-modern past, but also serves to promote a neo-modernization theory of the history of early industrialization. The goal of this article is to ask whether an admittedly anachronistic term such as 'expertise' can be a useful and illuminating concept in studying early modern history; whether it can do so without warping our view of the past beyond recognition; and whether it can be decoupled from current versions of modernization theory and other whiggish historical notions.